2017
DOI: 10.1177/2192568217700100
|View full text |Cite
|
Sign up to set email alerts
|

Use of Intraoperative Ultrasound During Spinal Surgery

Abstract: Study Design:Review and technical report.Objective:Intraoperative ultrasound has been used by spine surgeons since the early 1980s. Since that time, more advanced modes of intraoperative imaging and navigation have become widely available. Although the use of ultrasound during spine surgery has fallen out of favor, it remains the only true real-time imaging modality that allows surgeons to visualize soft tissue anatomy instantly and continuously while operating. It is our objective to demonstrate that for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 55 publications
(95 reference statements)
0
21
1
Order By: Relevance
“…Hence, image guidance such as navigation system or intra-operative ultra sound could be considered the most reliable methods to visualize the ventral epidural space and assess restoring of the ventral CSF space as reported by Vasudeva et al and Kelly at al. [22] , [107] , [108] .…”
Section: Evolution In Surgerymentioning
confidence: 99%
“…Hence, image guidance such as navigation system or intra-operative ultra sound could be considered the most reliable methods to visualize the ventral epidural space and assess restoring of the ventral CSF space as reported by Vasudeva et al and Kelly at al. [22] , [107] , [108] .…”
Section: Evolution In Surgerymentioning
confidence: 99%
“…A spinal cord surgery, is known as a sensitive and delicate one, with a high risk of post-surgical adverse effects [6][7][8]. These surgeries are planned, using data from images of a pre-operative Computer Tomography Image's (CTI) and/or Magnetic Resonance Image's (MRI) [9,10] and also from a Planar X-ray Image (PXI) (performed at the beginning of the surgery, when the patient is already anesthetized and in the 'surgical position').…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary study using US was reported on newborns [7,8], for in-vitro studies, where a complete tumor resection was reported [16]. It was also applied during laminoplasty, as it is a useful method for evaluating spinal cord decompression status [12].…”
Section: Introductionmentioning
confidence: 99%
“…18 , 21 , 22 Advances have occurred in many aspects of ultrasound technology including sensors, computer hardware, and software. It is used in spinal applications, 23 , 24 and has even been used in the cervical spine in outer space. 25 , 26 …”
mentioning
confidence: 99%
“…A recent review summarized the use of ultrasound in spinal diagnostic and therapeutic applications 27 and another reviewed the use of ultrasound in spine surgery, 24 claiming the use of intraoperative ultrasound was mainly for tumors or calcified thoracic discs. A more recent study reported the clinical evaluation of ultrasound for lateral lumbar spine surgery.…”
mentioning
confidence: 99%